The Effect of Rubber Ball Pair Drills on Volleyball Underhand Passing Skills of Fifth Grade Students - Noor Reza Alfauzi; Rohmad Apriyanto; Mohamad Da’i; Afdol Febriansyah (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2026)
This study aims to determine the effect of the paired training method using a rubber ball on the underhand passing skills in volleyball in 5th grade students of Tanjungharjo Elementary School. The method used is a quasi-experimental design with a One Group Pretest-Posttest Design, where students are given training in underhand passing using a rubber ball and their abilities are measured before and after treatment through a 60-second performance test. This study used a sample of 15 fifth grade students. The results showed a significant increase in underhand passing skills, with an average value increasing from 20.27 to 32.87. Based on the normality test, the data were normally distributed (p>0.05) so that data analysis was carried out using the parametric statistical analysis. Data were analyzed using descriptive statistics and a paired sample T-Test, which produced a significance value (p-value) of 0.000 (<0.05) so that the null hypothesis was rejected and a significant effect was proven. The rubber ball media provides a sense of security and comfort for students, thereby increasing their courage to practice, while the paired training method strengthens the formation of motor memory through systematic repetition of movements. In conclusion, the use of rubber balls with the pair training method significantly improves students' underhand passing skills and is recommended as an effective learning approach in elementary schools.